THE CORRELATION OF COMMUNITY KNOWLEDGE LEVELS ABOUT FIRST AID IN CONDITIONS OF UNCONSCIOUSNESS WITH COMMUNITY READINESS TO PROVIDE BASIC LIFE SUPPORT IN DUKUHKARYA VILLAGE IN 2022 - Dwifia Nahrudin, Lita; Arabta M. Peraten Pelawi; Lina Indrawati (Soscience: Jurnal Ilmu Sosial Science, 2025)
Basic life support is a basic aspect of rescue measures related to cardiac arrest. Basic life support can be taught to anyone. Providing and evaluating basic life support in the prehospital range can occur anywhere at any time, so the role special lay people  and health members is expected to be able to take action to handle emergency conditions. Cardiac arrest is a condition where the mechanical function of the heart suddenly stops, which is reversible with appropriate treatment but will cause death if not treated immediately. Community knowledge is generally good in performing basic life support. The research method used is quantitative with cross-sectional analytic research. The population in this study is the community of Rt 001 Rw 001 totaling 104 respondents. The data collection technique was using purposive sampling. It was found that with a significant level of 100% or a value of 5% (0.05) the Chi Square test results obtained p value (0.000) < value (0.05). There is a correation of the level of community knowledge about first aid in an unconscious condition with the community's readiness to carry out basic life support in Dukuhkarya Village in 2022. There is a  the correlation of community knowledge about first aid in an unconscious condition with the community's readiness to carry out basic life support in Dukuhkarya Village in 2022. There is a  the correlation of community knowledge about first aid in an unconscious condition with the community's readiness to carry out basic life support in Dukuhkarya Village in 2022.